The impact of human complement on the clinical outcome of malaria infection. (November 2022) - Reiss, Timo; Müller, Felix; Pradel, Gabriele
Abstract: The tropical disease malaria remains a major cause of global morbidity. Once transmitted to the human by a blood-feeding mosquito, the unicellular malaria parasite comes into contact with the complement system and continues to interact with human complement during its intraerythrocytic replication cycles. In the course of infection, both the classical and the alternative pathway of complement are activated, leading to parasite opsonization and lysis as well as the induction of complement-binding antibodies. While complement activity can be linked to the severity of malaria, it remains to date unclear, whether human complement is beneficial for protective immunity or if extensive complement reactions may rather enhance pathogenesis. In addition, the parasite has evolved molecular strategies to circumvent attack by human complement and has even developed means to utilize complement factors as mediators of host cell infection. In this review, we highlight current knowledge on the role of human complement for the progression of malaria infection. We discuss the various types of interactions between malaria parasites and complement factors with regard to immunity and infection outcome and set a special emphasis on the dual role of complement in the context of parasite fitness. Highlights: The human complement system is highly active during malaria infection. High levels of C1q-fixing antibodies are associated with reduced risk of severe malaria. Red blood cell-resident CR1 is linked to the severity of malaria. C5a-mediated dysregulation of inflammation plays a key role in placental malaria. The co-option of human complement regulators is a key immune evasion mechanism of malaria parasites.